TINJAUAN HUKUM TANDA TANGAN ELEKTRONIK (DIGITAL SIGNATURE) DALAM PERJANJIAN DAN TRANSAKSI ELEKTRONIK (E-COMMERCE) - Suwardi; Nur Habib Rubai (Universitas Muhammadiyah Kotabumi, 2020)
This study discusses the Legal Review Analysis of the Use of Electronic Signatures (Digital Signature) in Electronic Agreements and Transactions (E-Commerce). In information gathering strategy, the writer uses a writing concentrate approach, which is the single technique used in standardizing halal exploration. Where the writer searches for and then researches, studies, analyzes, sorts, codes material or writing in the library and then turns it into the purpose of the examination to be discussed. The results of the research found that the position and legal power of electronic marks as evidence can be considered substantial with the assumption that the electronic mark uses an electronic structure that is in accordance with the laws and regulations in Indonesia. This refers to Article 11 of Government Regulation Number 11 of 2008 concerning Electronic and Information Trading. These guidelines state an endorsement that regardless of whether it is simply a code, an electronic mark has legal force and legal effect. The requirements as referred to in Article 11 of the ITE Guidelines are essential requirements that must be met for every electronic brand. Electronic evidence for this condition electronic alerts can have great power if the information is undeniable, representable, possible, and proven, further demonstrating what happened. Confirmation of the appearance of the power individual must have the option to provide information in his possession is from the beginning of the secret electrical framework